CLINICAL CASE: OPPORTUNITY OF THERAPY OPTIMIZATION DUE TO TRANSITIONING FROM SILDENAFIL TO RIOCIGUAT IN PATIENT WITH IDIOPATHIC PULMONARY HYPERTENSION - I. N. Taran; V. M. Paramonov; Z. S. Valieva; M. A. Saidova; S. N. Nakonechnikov; T. V. Martynyuk; I. Ye. Chazova (Евразийский Кардиологический Журнал)
SUMMERY The patient with diagnosis of idiopathic pulmonary hypertension, functional class III (WHO) was treated by anticoagulants, diuretics. After 6 months of treatment with phosphodiesterase type 5-inhibitor sildenafil, there was observed the negative dynamic with systolic pulmonary arterial pressure, intolerance to exercises. The treatment goals were not achieved with sildenafil therapy. The transitioning from sildenafil to riociguat therapy was done. By 6 months of the riociguat therapy there was achieved the significant improvement of the functional and hemodynamic status. Ам^^ to the stratification risk scale the treatment goals were reached. Keywords: idiopathic pulmonary hypertension, phosphodiester-ase type 5 inhibitor, sildenafil, soluble guanylate cyclase stimulators, riociguat, risk assessment.